ChemInform Abstract: An Organocatalytic Synthesis of N‐Sulfonyl Imines Using Chloramine‐T in Aqueous Medium. Issue 47 (6th November 2014) - Chawla, Ruchi; Singh, Atul K.; Yadav, Lal Dhar S.
Abstract The novel protocol using L‐proline as an organocatalyst allows the synthesis of N‐sulfonyl imines from aldehydes and chloramine‐T under mild conditions.